Karakteristik Pemakzulan Presiden di Indonesia - Catur Alfath Satriya (Jurnal Konstitusi, 2022)
One of the features of the presidential system is the process of presidential impeachment. Before the amendment, Indonesia did not have a clear mechanism to impeach the president in the middle of his term. The impeachment of the president is determined by a majority vote in the People’s Consultative Assembly. This is a problem because the impeachment of the president only uses a political process, and there is no legal process in it. After the amendment, the presidential impeachment concept was born that in a presidential system, the president cannot be dismissed only through a political process; there must be a legal process before the political process. Based on the analysis, the process of presidential impeachment in Indonesia does not follow the principle of checks and balances. This is because the impeachment process for the president in Indonesia does not involve the second chamber in the process